Association of Iron Depletion with Menstruation and Dietary Intake Indices in Pubertal Girls: The Healthy Growth Study. (23rd December 2013) - Moschonis, George; Papandreou, Dimitrios; Mavrogianni, Christina; Giannopoulou, Angeliki; Damianidi, Louisa; Malindretos, Pavlos; Lionis, Christos; Chrousos, George P.; Manios, Yannis
Abstract : The aim of the present study was to investigate the associations of iron depletion (ID) with menstrual blood losses, lifestyle, and dietary habits, in pubertal girls. The study sample comprised 1222 girls aged 9–13 years old. Biochemical, anthropometrical, dietary, clinical, and physical activity data were collected. Out of 274 adolescent girls with menses, 33.5% were found to be iron depleted (defined as serum ferritin < 12 μ g/L) compared to 15.9% out of 948 girls without menses. Iron-depleted girls without menses were found to have lower consumption of poultry (P = 0.017 ) and higher consumption of fruits (P = 0.044 ) and fast food (P = 0.041 ) compared to their peers having normal iron status. Multivariate logistic regression analysis showed that girls with menses were 2.57 (95% CI: 1.37, 4.81) times more likely of being iron depleted compared to girls with no menses. Iron depletion was found to be associated with high calcium intake, high consumption of fast foods, and low consumption of poultry and fruits. Menses was the only factor that was found to significantly increase the likelihood of ID in these girls. More future research is probably needed in order to better understand the role of diet and menses in iron depletion.